Evaluation of the UV/H2O2 system for treating natural water with a mixture of anthracene and benzo[a]pyrene at ultra-trace levels (2018)
The presence of polycyclic aromatic hydrocarbons, such as anthracene (AN) and benzo[a]pyrene (BaP), in water has become a problem of great concern due to the detrimental health effects caused to humans and living beings. In this work, the efficiency of the UV/H2O2 system for degrading the target compounds at ultra-trace levels in surface water has been evaluated. For this purpose, a previous optimization step using a face-centered central composite experimental design has been conducted, considering the effect of the UV-C irradiance and the initial concentration of H2O2. It was evidenced that under optimal operating conditions (11 mg L−1 H2O2 and 0.63 mW cm−2 irradiance), AN and BaP removal percentages were higher than 99.8%. Additionally, 69.3% of the organic matter, in terms of total organic carbon, was mineralized without the production of transformation by-products more harmful than the parent compounds. These findings demonstrate the oxidation capacity of the examined system in a natural matrix for degrading micropollutants that cannot be converted through conventional treatment processes. Consequently, new horizons are opened for the effective use of the UV/H2O2 system for drinking water production, providing the accomplishment of other regulated parameters related to water quality.